Pengaruh Model Pembelajaran Quantum Learning terhadap Sikap Percaya Diri Siswa dalam Pembelajaran Ilmu Pengetahuan Sosial di Madrasah Tsanawiyah Al-Muttaqin Pekanbaru - Irma Fitriani; Devi Arisanti; Sakilah Sakilah; Alimuddin Alimuddin; Wardani Purnama Sari (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
This research aimed at finding out the effect of Quantum Learning model toward student self-confidence in Social Science learning at Islamic Junior Hight School of Al-Muttaqin Pekanbaru. Two classes, IX.C (experimental) and IX.G (control), were chosen using purposive sampling and a quantitative quasi-experimental design. Observation, surveys, and documentation were used to gather data, and Excel and SPSS 25 were used to analyze the results using t-tests, effect size, and N-Gain. Results indicated that the experimental group's self-confidence (mean = 86.76) was significantly higher than that of the control group (mean = 80.38), with a p-value of 0.000 (< 0.05), a moderate effect size of 0.51, and an N-Gain of 42.33% (moderate) vs 10.66% (low). These results attest to the Quantum Learning model's efficacy in raising students' self-convidence.